BRCA2 mutation analysis in male breast cancer patients in Poland - Karczewska, Aldona; Mackiewicz, Andrzej; Bręborowicz, Danuta; Godlewski, Dariusz; Kwiatkowska, Eliza; M. Lamperska, Katarzyna; Teresiak, Marek; Stawicka, Małgorzata; J. Krzyżosiak, Włodzimierz (Contemporary Oncology/Współczesna Onkologia, 2001)
Breast cancer is a rare disease in men. Germ-line mutations in BRCA2 and androgen receptor (AR) genes are thought to be responsible for a proportion of male breast cancer cases. The present study was performed on a series of 38 consenting patients not selected for family history of breast/ovarian cancer. The entire coding region of the BRCA2 gene was analyzed for germ-line mutations to evaluate the association between BRCA2 gene and male breast cancer in Poland. We identified five frameshift mutations (13%) and five missense unclassified variants (13%) of the BRCA2 gene. The frequencies of missense alterations were examined in a set of 200 chromosomes. Six of 38 patients (16%) had a family history of breast cancer, in one first- or second-degree relative, including two mutation carriers. The results of this study suggest that germ-line BRCA2 mutations account for moderate proportion of male breast cancer in Poland.